Do seizures compromise correction maintenance after spinal fusion in cerebral palsy scoliosis?. Issue 6 (November 2020) - Abousamra, Oussama; Sullivan, Brian T.; Shah, Suken A.; Yaszay, Burt; Samdani, Amer F.; Cahill, Patrick J.; Newton, Peter O.; Sponseller, Paul D.
Abstract : Seizure disorder in cerebral palsy (CP) has been described as a risk factor for postoperative complications after posterior spinal fusion. However, the effect of seizures on the maintenance of curve correction has not been reported. The aim of this study is to investigate associations between seizure history and maintenance of curve correction after posterior spinal fusion in children with CP. We analyzed records of 201 children with CP who underwent posterior spinal fusion with two-year follow-up. Patients were classified as having no seizures (31%); controlled seizures (54%); or poorly controlled seizures (PCS, 15%). Perioperative data, radiographic measurements, and complications were compared between groups. Groups were similar in operative time, estimated blood loss, and rates of deep wound infection and implant-related complications. The PCS group had a higher rate of respiratory complications (27%) than the no seizures (10%; P = 0.03) and controlled seizures (12%; P = 0.04) groups. Controlled seizures and PCS groups had longer ICU stays than the no seizures group ( P = 0.02 and P = 0.04). Major coronal curve and pelvic obliquity were corrected significantly in all groups, and correction was maintained at 2 years. Loss of correction during follow-up was similar between groups. Although seizures were associated with longer ICU stays and more respiratory complications, there was no association between seizure history and loss of curve correction at two years of follow-up after CP scoliosis surgery.